Veterinary Prescriptions of Antibiotics Approved for Human Use: A Five-Year Analysis of Companion Animal Use and Regulatory Gaps in Brazil - Rana Zahi Rached; Regina Albanese Pose; Érika Leão Ajala Caetano; Joana Garrossino Magalhães; Denise Grotto (Veterinary Sciences)
Antimicrobial resistance (AMR) is a growing global concern, influenced by antibiotic use in both human and veterinary medicine, especially in companion animals. In low- and middle-income countries, regulatory oversight on veterinary prescriptions is often limited, creating gaps that can accelerate AMR. This study aimed to characterize the use of antibiotics approved for human use that are prescribed by veterinarians for companion animals in Brazil, a country representative of broader regulatory challenges. We conducted a retrospective analysis of five years (2017–2021) of national sales data recorded by the National System for the Management of Controlled Products (SNGPC), maintained by the Brazilian Health Regulatory Agency (ANVISA). A total of 789,893 veterinary antibiotic prescriptions were analyzed over the five-year period, providing a comprehensive overview of prescribing patterns. The dataset included all oral and injectable antibiotics purchased in human pharmacies with veterinary prescriptions. Data wrangling and cleaning procedures were applied to extract information on volume, antibiotic classes, seasonal variation, and regional distribution. The results revealed a predominance of penicillins, first- and second-generation cephalosporins, and a marked increase in macrolide use, especially azithromycin. Notable regional disparities were observed, with the southeastern region leading in prescription volume. The findings, particularly the disproportionate use of azithromycin and the marked regional disparities, highlight the need for targeted monitoring policies and a stricter regulation of off-label antibiotic use in veterinary medicine. They also offer insights applicable to other countries facing similar AMR threats due to limited surveillance and regulatory frameworks.